Comparative Effectiveness of Calabadion and Sugammadex to Reverse Non-depolarizing Neuromuscular-blocking Agents. (December 2015) - Haerter, Friederike; Simons, Jeroen Cedric Peter; Foerster, Urs; Moreno Duarte, Ingrid; Diaz-Gil, Daniel; Ganapati, Shweta; Eikermann-Haerter, Katharina; Ayata, Cenk; Zhang, Ben; Blobner, Manfred; Isaacs, Lyle; Eikermann, Matthias
Abstract : Background: The authors evaluated the comparative effectiveness of calabadion 2 to reverse non-depolarizing neuromuscular-blocking agents (NMBAs) by binding and inactivation. Methods: The dose–response relationship of drugs to reverse vecuronium-, rocuronium-, and cisatracurium-induced neuromuscular block (NMB) was evaluated in vitro (competition binding assays and urine analysis), ex vivo (n = 34; phrenic nerve hemidiaphragm preparation), and in vivo (n = 108; quadriceps femoris muscle of the rat). Cumulative dose–response curves of calabadions, neostigmine, or sugammadex were created ex vivo at a steady-state deep NMB. In living rats, the authors studied the dose–response relationship of the test drugs to reverse deep block under physiologic conditions, and they measured the amount of calabadion 2 excreted in the urine. Results: In vitro experiments showed that calabadion 2 binds rocuronium with 89 times the affinity of sugammadex (Ka = 3.4 × 10 9 M −1 and Ka = 3.8 × 10 7 M− 1 ). The results of urine analysis (proton nuclear magnetic resonance), competition binding assays, and ex vivo study obtained in the absence of metabolic deactivation are in accordance with an 1:1 binding ratio of sugammadex and calabadion 2 toward rocuronium. In living rats, calabadion 2 dose-dependently and rapidly reversed all NMBAs tested. The molar potency of calabadion 2 to reverse vecuronium and rocuronium was higher compared with that of sugammadex. Calabadion 2 was eliminated renally and did not affect blood pressure or heart rate. Conclusions: Calabadion 2 reverses NMB induced by benzylisoquinolines and steroidal NMBAs in rats more effectively, i.e., faster than sugammadex. Calabadion 2 is eliminated in the urine and well tolerated in rats. Abstract : Calabadion 2 rapidly reversed deep rocuronium-, vecuronium-, and cisatracurium-induced neuromuscular blockade in a dose-dependent manner. Calabadion 2 reversed rocuronium- and vecuronium-induced neuromuscularblockade with a 1:1 binding ratio, like sugammadex, but it had a higher in vitro binding affinity and a higher molar potency in vivo.